2009
DOI: 10.1111/j.1471-4159.2009.05999.x
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory response in the MPTP model of Parkinson’s disease is mediated by brain angiotensin: relevance to progression of the disease

Abstract: The neurotoxin MPTP reproduces most of the biochemical and pathological hallmarks of Parkinson’s disease. In addition to reactive oxygen species (ROS) generated as a consequence of mitochondrial complex I inhibition, microglial NADPH‐derived ROS play major roles in the toxicity of MPTP. However, the exact mechanism regulating this microglial response remains to be clarified. The peptide angiotensin II (AII), via type 1 receptors (AT1), is one of the most important inflammation and oxidative stress inducers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
170
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(185 citation statements)
references
References 45 publications
14
170
0
1
Order By: Relevance
“…Experimental data also support the involvement of brain RAS in dopaminergic degeneration [110,111,112]. It was demonstrated that AII increased the neurotoxic effect induced by low doses of 6-OHDA, and the treatment with inhibitors of ACE [113,114,112] or blockage of AT1Rs [98,95,96] resulted in a significant reduction of both the loss of dopaminergic neurons and the levels of protein oxidation and lipid peroxidation induced by the neurotoxins [115]. Furthermore antagonist of AT1Rs has been shown to be neuroprotective [116].…”
Section: Renin-angiotensin Systemmentioning
confidence: 79%
See 3 more Smart Citations
“…Experimental data also support the involvement of brain RAS in dopaminergic degeneration [110,111,112]. It was demonstrated that AII increased the neurotoxic effect induced by low doses of 6-OHDA, and the treatment with inhibitors of ACE [113,114,112] or blockage of AT1Rs [98,95,96] resulted in a significant reduction of both the loss of dopaminergic neurons and the levels of protein oxidation and lipid peroxidation induced by the neurotoxins [115]. Furthermore antagonist of AT1Rs has been shown to be neuroprotective [116].…”
Section: Renin-angiotensin Systemmentioning
confidence: 79%
“…The components involved in the effects of AII in peripheral tissues such as NADPH-oxidase have also been found in neurons [91] and glial cells [92,93]. It has been demonstrated the presence of different cytoplasmic and membrane subunits of the NADPH complex in mesencephalic DAergic neurons, astrocytes and microglia [94,95,96]. NADPH-oxidase complex is the most significant source of ROS other that mitochondria [97].…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we show that morin attenuated MPP + -induced loss of cell viability and apoptosis in PC12 cells, suggesting that morin is a potential therapeutic molecule for the treatment of neurodegenerative diseases. MPP + has been shown to induce oxidative stress in vitro and in vivo [25][26][27] . In agreement with its antioxidant activity [24,28] , morin attenuated ROS formation.…”
Section: Discussionmentioning
confidence: 99%